Study on flow field characteristics of undulating member bar in engineering. Issue 1 (June 2021) - Zhao, Ruochen; Zhao, Meng; Liu, Zhen; Jia, Tiemei; Kong, Fanguang
Abstract: Aiming at the undulating member bar, three kinds of wavelength models are established. The flow characteristics of the undulating member bar with space angle of attack are analyzed by the large eddy simulation method under high Reynolds number, its velocity and pressure distribution with different wavelengths are studied, and the time and frequency domain characteristics of circumferential pressure coefficient, resistance and lift are discussed. The results suggest that the greater the fluctuation of the outer surface of the wave member, the greater the time difference between the maximum and minimum cross-sections; the greater the surface inclination, the greater the change in surface pressure. While the smaller the wavelength, the larger the amplitude of the rod resistance coefficient and the range of the main peak; the larger the wavelength, the slower the attenuation rate of the amplitude peak of the rod resistance and lift coefficient. Combined with the characteristics of the flow field, when the incoming flow has a space angle of attack, the wave cylinder of can achieve a better effect of drag reduction and vibration reduction. Finally, the research results provide important significance and value for the research and application of the flow characteristics of undulating member bar.